2013
DOI: 10.1186/1471-2296-14-178
|View full text |Cite
|
Sign up to set email alerts
|

Primary care nurses’ experiences of how the mass media influence frontline healthcare in the UK

Abstract: BackgroundMass media plays an important role in communicating about health research and services to patients, and in shaping public perceptions and decisions about health. Healthcare professionals also play an important role in providing patients with credible, evidence-based and up-to-date information on a wide range of health issues. This study aims to explore primary care nurses’ experiences of how mass media influences frontline healthcare.MethodsIn-depth telephone interviews were carried out with 18 prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…29 Among the cohort in the current study, the level of knowledge regarding age as a risk factor for CHD was close to the cut-off point designating adequate knowledge, reflecting a limited understanding of age as a non-modifiable risk factor for CHD. Furthermore, while the majority of the participants knew that being overweight increased the risk of CHD, fewer realised that carrying higher levels of abdominal fat imposes the greatest risk.…”
Section: Discussionmentioning
confidence: 72%
“…29 Among the cohort in the current study, the level of knowledge regarding age as a risk factor for CHD was close to the cut-off point designating adequate knowledge, reflecting a limited understanding of age as a non-modifiable risk factor for CHD. Furthermore, while the majority of the participants knew that being overweight increased the risk of CHD, fewer realised that carrying higher levels of abdominal fat imposes the greatest risk.…”
Section: Discussionmentioning
confidence: 72%
“…The continued modification of procedures also demands constant public engagement efforts to avoid dissemination of conflicting messages and to ensure that information released is up to date and presented at a level that can be adequately understood. Because there have been limited national communication campaigns in non–EVD-affected countries, it is likely that other outlets, including traditional mass media and social media, might have been used by the public to meet their information needs ( 13 ), with probable trade-offs between immediacy and accuracy or reliability of information provided. The variation of readability identified in our study suggests that with contributions from health literacy specialists, public health agencies could further adapt the EVD information provided.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that the controversial health-related information reported in the media might affect patients’ perceptions of and decision making about medical care [27]. In addition, several studies have shown that health-related information on the Internet is less likely to be accredited by the Health on the Net Foundation, and is therefore less reliable [28].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, patients who spend more time using the Internet may be more likely to visit outpatient clinics for clarification and interpretation of a kaleidoscope of health-related information. This, therefore, may increase physicians’ workloads, as they have to spend additional time discussing health-related information and reassuring patients [27]. …”
Section: Discussionmentioning
confidence: 99%